First insights in the variability of Borrelia recurrentis genomes. - Durdica Marosevic; Gabriele Margos; Reinhard Wallich; Andreas Wieser; Andreas Sing; Volker Fingerle (PLoS Neglected Tropical Diseases, 2017)
Background Borrelia recurrentis is the causative agent of louse-borne relapsing fever, endemic to the Horn of Africa. New attention was raised in Europe, with the highest number of cases (n = 45) reported among migrants in 2015 in Germany and sporadically from other European countries. So far only one genome was sequenced, hindering the development of specific molecular diagnostic and typing tools. Here we report on modified culture conditions for B. recurrentis and the intraspecies genome variability of six isolates isolated and cultured in different years in order to explore the possibility to identify new targets for typing and examine the molecular epidemiology of the pathogen. Methodology/principal findings Two historical isolates from Ethiopia and four isolates from migrants from Somalia (n = 3) and Ethiopia (n = 1) obtained in 2015 were cultured in MPK-medium supplemented with 50% foetal calf serum. Whole DNA was sequenced using Illumina MiSeq technology and analysed using the CLC Genomics Workbench and SPAdes de novo assembler. Compared to the reference B. recurrentis A1 29-38 SNPs were identified in the genome distributed on the chromosome and plasmids. In addition to that, plasmids of differing length, compared to the available reference genome were identified. Conclusions/significance The observed low genetic variability of B. recurrentis isolates is possibly due to the adaptation to a very conserved vector-host (louse-human) cycle, or influenced by the fastidious nature of the pathogen and their resistance to in vitro growth. Nevertheless, isolates obtained in 2015 were bearing the same chromosomal SNPs and could be distinguished from the historical isolates by means of whole genome sequencing, but not hitherto used typing methods. This is the first study examining the molecular epidemiology of B. recurrentis and provides the necessary background for the development of better diagnostic tools.